Grinding blank assembly

By optimizing the performance indicators of the adhesive composition, the vibration problem of the ground blank assembly in the CAD/CAM machining machine was solved, achieving higher processing accuracy and environmentally friendly product packaging.

CN121463931APending Publication Date: 2026-02-03KURARAY NORITAKE DENTAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480045823.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2024-08-02
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

The existing grinding blank assembly cannot adequately mitigate vibrations when processed using a CAD/CAM machine, resulting in reduced processing accuracy.

Method used

By adjusting the performance parameters of the adhesive composition, such as the loss coefficient tanδ, storage modulus E', loss elastic modulus E”, and the ratio of peel bond strength to fracture strain (X1/Y1), to meet specific ranges, vibrations during processing can be mitigated and processing accuracy improved.

Benefits of technology

It effectively mitigates vibrations during processing, improves processing accuracy, reduces vibrations during product transportation, and lowers environmental burden and material requirements for product packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121463931A_ABST
    Figure CN121463931A_ABST
Patent Text Reader

Abstract

The present invention provides a polishing blank assembly that mitigates vibrations generated during processing by a CAD / CAM processing machine and has excellent processing accuracy. The present invention pertains to a polishing blank assembly which comprises a part to be processed, a holding part, and an adhesive composition, and which satisfies the following conditions (1) and / or (2): (1) the loss coefficient (tan [delta]) of a cured product of the adhesive composition at 20 DEG C in an ultra-micro indentation test (nanoindenter) is 0.70 or less; and (2) the ratio (X1 / Y1) of the peel adhesive strength (X1) to the fracture strain (Y1) in a compression shear adhesive test at 20 DEG C of the part to be processed and the holding part is 1200 N / mm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an abrasive blank assembly comprising a workpiece portion, a retaining portion and an adhesive composition.

[0002] More specifically, it relates to an abrasive blank assembly comprising a workpiece, a retaining part, and an adhesive composition, which can mitigate vibrations generated during machining using a CAD / CAM machine and improve machining accuracy. Background Technology

[0003] The abrasive blank assembly used in dental applications consists of a holder fixed to a processing machine, a workpiece, and an adhesive that bonds them together. To prevent the workpiece from detaching from the holder during processing and thus failing to obtain the desired patch, the adhesive uses a resin that firmly bonds the holder to the workpiece (see Patent Documents 1-3, etc.).

[0004] For example, Patent Document 1 discloses a zirconia polished blank containing an epoxy adhesive and a cyanoacrylate adhesive.

[0005] Patent Document 2 discloses an adhesive composition comprising 2-cyanoacrylate and a specific (meth)acrylate or (meth)acrylamide compound.

[0006] In addition, Patent Document 3 discloses a grinding blank assembly with a low risk of falling off by giving the support part a specific surface roughness and surface properties.

[0007] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2020-151235 Patent Document 2: Japanese Patent Application Publication No. 2018-76272 Patent document 3: Japanese Patent Application Publication No. 2020-068873. Summary of the Invention

[0008] The problem that the invention aims to solve The grinding blank assemblies disclosed in Patent Documents 1-3 use adhesive compositions with high elastic modulus for the purpose of strong bonding.

[0009] However, the inventors have discovered the following problem: when the grinding blank assembly disclosed in Patent Documents 1 to 3 is processed using a CAD / CAM machine, it cannot adequately mitigate the vibration caused by the rotation of the grinding rod during processing, thus reducing the processing accuracy.

[0010] The purpose of this invention is to provide a grinding blank assembly that mitigates vibrations generated during machining using a CAD / CAM machine and achieves excellent machining accuracy.

[0011] means for solving problems In order to solve the above-mentioned problems, the inventors conducted repeated and in-depth research and found that in the stress-strain curve of the compression shear bonding test between the processed part and the holding part, by making the ratio of the shear force at the time of fracture to the displacement before fracture within a specified range, it is possible to mitigate the vibration generated during processing using a CAD / CAM machine. Based on this insight, further research was conducted, and the present invention was completed.

[0012] The present invention includes the following technical solutions.

[0013] [1] A grinding blank assembly comprising a workpiece, a retaining portion and an adhesive composition, and satisfying the following conditions [1] and / or [2]: [1] The cured adhesive composition has a loss coefficient tanδ of less than 0.70 at 20°C in an ultra-micro indentation test (nanoindenter); [2] The ratio (X1 / Y1) of the peel bond strength (X1) and the fracture strain (Y1) of the processed part and the retaining part in the compression shear bonding test at 20°C is less than 1200 N / mm.

[0014] [2] According to the grinding blank assembly described in [1], wherein the storage modulus E' of the cured product of the aforementioned adhesive composition at 20°C in the ultra-micro indentation test is 200 N / mm². 2 the following.

[0015] [3] According to the grinding blank assembly described in [1] or [2], wherein the cured product of the aforementioned adhesive composition has a loss elastic modulus E” of 100 N / mm² at 20 °C in an ultra-micro indentation test. 2 the following.

[0016] [4] According to the grinding blank assembly described in [1], wherein the peel bond strength (X1) at 20°C in the aforementioned compression shear bonding test is 100N or more.

[0017] [5] The grinding blank assembly according to [1] or [4], wherein the fracture strain (Y1) at 20°C in the aforementioned compression shear bonding test is 0.38~1.0 mm.

[0018] [6] The grinding blank assembly according to any one of [1] to [5], wherein the aforementioned adhesive composition forms a layer held between the processed portion and the holding portion. The thickness of the aforementioned layer is 5~500μm.

[0019] [7] The grinding blank assembly according to any one of [1] to [6], wherein the Vickers hardness of the aforementioned processed part, as measured according to JIS Z 2244:2009, is 40 to 140 HV 5 / 30.

[0020] [8] The grinding blank assembly according to any one of [1] to [7], wherein the aforementioned adhesive composition comprises at least one selected from epoxy-modified silicone compounds, (meth)acrylic compounds and urethane compounds (excluding cyanoacrylate compounds).

[0021] [9] The grinding blank assembly according to any one of [1] to [8], wherein the aforementioned processed part comprises oxide ceramic.

[0022]

[10] The grinding blank assembly according to any one of [1] to [9], wherein the aforementioned processed part comprises at least one selected from zirconium oxide, alumina and glass ceramics.

[0023]

[11] The grinding blank assembly according to any one of [1] to

[10] , wherein the aforementioned retaining part comprises an aluminum alloy and / or an iron alloy.

[0024]

[12] The grinding blank assembly according to any one of [1] to

[11] is used for dental purposes.

[0025] The method for manufacturing the grinding blank assembly as described in any one of

[13] [1] to

[12] includes a step of curing an adhesive composition to bond the part to be processed to the holding part. The aforementioned adhesive composition is any of the following (excluding cyanoacrylate compounds).

[0026] (i) A mixture obtained by mixing epoxy resin with an organosilicon-modified polymer; (ii) A mixture obtained by mixing (meth)acrylic monomers and / or (meth)acrylic oligomers with modified organosilicon; or (iii) At least one carbamate compound.

[0027] Invention Effects According to the present invention, a grinding blank assembly that mitigates vibrations generated during machining using a CAD / CAM machine and provides excellent machining accuracy can be provided.

[0028] In addition, since it can also effectively mitigate vibrations during product transportation, it can reduce the amount of cushioning material used when packaging products, thereby reducing environmental impact and / or minimizing product boxes. Attached Figure Description

[0029] Figure 1 This is a schematic diagram illustrating a grinding blank assembly according to one embodiment of the present invention.

[0030] Figure 2 This is a graph illustrating the stress-strain curve in a compression-shear bonding test of the grinding blank assembly according to one embodiment of the present invention. Detailed Implementation

[0031] The grinding blank assembly of the present invention comprises a workable portion, a holding portion and an adhesive composition, and satisfies the following conditions [1] and / or [2].

[0032] [1] The cured adhesive composition has a loss coefficient tanδ of less than 0.70 at 20°C in an ultra-micro indentation test (nanoindenter); [2] The ratio (X1 / Y1) of the peel bond strength (X1) and the fracture strain (Y1) of the processed part and the retaining part in the compression shear bonding test at 20°C is less than 1200 N / mm.

[0033] In this specification, the methods for determining and calculating the loss coefficient tanδ, storage modulus E', and loss elastic modulus E” of the cured adhesive composition at 20°C in an ultramicro indentation test (nanoindenter) are as described in the examples below.

[0034] It should be noted that the upper and lower limits of the numerical ranges (content of each component, values ​​calculated from each component, and physical properties, etc.) in this specification can be appropriately combined.

[0035] The grinding blank assembly of the present invention, by giving the adhesive composition the minimum elastic properties required during processing and increasing the adhesive properties, can mitigate vibrations generated during processing using a CAD / CAM machine, mitigate the difference in vibration frequencies between the processed part and the holding part, and ensure processing accuracy when processing the processed part to obtain a patch.

[0036] The grinding blank assembly of the present invention is as follows Figure 1 A and Figure 1 As shown in B, it includes a processed part (1), a holding part (2), and an adhesive composition (3).

[0037] When viewed axially from the retaining part (2), the adhesive composition (3) can be as follows: Figure 1 As shown in B, the coating can be applied only to the same area as the bottom surface of the retaining part (2), or as shown in B. Figure 1Alternatively, an adhesive composition may be applied to the entire mating surface of the processed part (1) that engages with the holding part (2), or a portion of the holding part (2) may be coated with the adhesive composition. Hereinafter, each embodiment will be described.

[0038] In one embodiment, the grinding blank assembly of the present invention includes a workable portion, a holding portion, and an adhesive composition, and satisfies condition [1]. Hereinafter, this embodiment will be referred to as the "first embodiment".

[0039] Regarding condition [1], specifically, the loss coefficient tanδ of the cured adhesive composition at 20°C in an ultra-micro indentation test (nanoindenter) is less than 0.70.

[0040] The aforementioned loss coefficient tanδ at 20°C is calculated using the storage modulus E' of the cured adhesive composition at 20°C and the loss elastic modulus E” of the cured adhesive composition at 20°C, by tanδ=E” / E'.

[0041] Hereinafter, the loss coefficient tanδ at 20℃, the storage modulus E' of the cured adhesive composition at 20℃, and the loss elastic modulus E” of the cured adhesive composition at 20℃ refer to the values ​​measured and calculated by ultra-micro indentation test on the cured adhesive composition.

[0042] Regarding the storage modulus E' of the cured material at 20°C (hereinafter also referred to as "storage modulus E'"), which is an elasticity index, from the viewpoints of mitigating vibrations during processing, increasing processing accuracy, and reducing the likelihood of separation between the workpiece and the holding part and / or partial separation of the workpiece during processing and / or transportation, the storage modulus E' of the cured material at 20°C is preferably 200 N / mm². 2 The following, and more preferably, is 150 N / mm 2 The following, and more preferably, is 120 N / mm 2 The following, the optimal value is 90 N / mm. 2 the following.

[0043] Furthermore, from the viewpoints of exhibiting viscosity while possessing the minimum elasticity required for processing, being able to mitigate vibrations generated during processing using a CAD / CAM machine, ensuring the processing accuracy of the patch, and mitigating the difference in vibration frequencies between the processed part and the holding part during transportation, the storage modulus E' is preferably 5 N / mm. 2 The above is preferred to be 8 N / mm. 2 The above is further optimized to 10 N / mm. 2 above.

[0044] Since the lower the storage modulus E' of the cured material at 20°C, the lower the elastic properties and the higher the viscous properties, the viscoelasticity of the cured material can be adjusted with this in mind.

[0045] Furthermore, from the viewpoint that the workpiece is less likely to detach from its self-holding part and / or partially detach from its workpiece under low temperature conditions, the energy storage modulus E' at -30°C is preferably within the same range as the energy storage modulus E' at 20°C mentioned above.

[0046] Regarding the loss modulus of elasticity E of the cured material at 20°C (hereinafter also referred to as "loss modulus of elasticity E"), from the viewpoints of exhibiting viscosity while possessing the minimum elasticity required for processing, being able to mitigate vibrations generated during processing using a CAD / CAM machine, ensuring the processing accuracy of the patch, and mitigating the difference in vibration frequencies between the processed part and the holding part during transportation, a value of 100 N / mm is preferred. 2 Below, 80 N / mm is preferred. 2 The following is a further preferred value: 50 N / mm 2 the following.

[0047] Furthermore, from the viewpoints of reducing elastic properties, increasing viscous properties, easily mitigating vibrations generated during machining using CAD / CAM machines, and mitigating the difference in vibration frequencies between the machined part and the holding part, the loss modulus E” is preferably 0.5 N / mm. 2 The above is preferred to be 1 N / mm. 2 The above is further optimized to 2N / mm. 2 above.

[0048] Furthermore, from the viewpoint that the workpiece is less likely to detach from its self-holding part and / or partially detach from its workpiece under low temperature conditions, the loss modulus E” at -30°C is preferably within the same range as the loss modulus E” at 20°C mentioned above.

[0049] From the viewpoints of mitigating vibrations during processing, increasing processing accuracy, and reducing the likelihood of separation between the workpiece and the holding part, and / or partial separation of the workpiece, during processing and / or transportation, the loss coefficient tanδ at 20°C (hereinafter also referred to as "loss coefficient tanδ at 20°C") measured by an ultra-micro indentation test is preferably 0.12 or more, more preferably 0.14 or more, and even more preferably 0.15 or more. Furthermore, tanδ is preferably 0.70 or less, more preferably 0.60 or less, even more preferably 0.55 or less, and even more preferably 0.50 or less.

[0050] Furthermore, from the viewpoint that the workpiece is less likely to detach from its self-holding part and / or partially detach from its workpiece under low temperature conditions, the loss coefficient tanδ at -30°C is preferably within the same range as the loss coefficient tanδ at 20°C mentioned above.

[0051] Furthermore, from the viewpoint that the workpiece is less likely to detach from its holding part and / or partially detach from its working part under low-temperature conditions, in a graph where the horizontal axis represents the measurement temperature and the vertical axis represents tanδ measured at each temperature, the peak of the loss coefficient tanδ is preferably located in a temperature range lower than the temperature at which the grinding blank is exposed during transportation and / or storage. The peak of the loss coefficient tanδ is preferably below 20°C, more preferably below 0°C, and even more preferably below -30°C.

[0052] In another embodiment, the grinding blank assembly of the present invention includes a workable portion, a holding portion, and an adhesive composition, and satisfies condition [2]. Hereinafter, this embodiment will be referred to as the "second embodiment".

[0053] Regarding condition [2], specifically, in the grinding blank assembly of the present invention, the ratio (X1 / Y1) of the peel bond strength (X1) (hereinafter also referred to as "peel bond strength (X1)" or "peel bond strength (X1) at 20°C") of the processing part and the holding part in the compression shear bond test at 20°C to the fracture strain (Y1) (hereinafter also referred to as "fracture strain (Y1)" or "fracture strain (Y1) at 20°C") in the test is 1200 N / mm or less.

[0054] From the viewpoint of mitigating vibrations during processing and increasing processing accuracy, the ratio (X1 / Y1) of the aforementioned peel bond strength (X1) to fracture strain (Y1) is preferably 1200 N / mm or less, more preferably 1150 N / mm or less, even more preferably 1100 N / mm or less, further preferably 1000 N / mm or less, and most preferably 900 N / mm or less.

[0055] Furthermore, from the viewpoint of mitigating vibrations during processing and increasing processing accuracy, the ratio of the aforementioned peel bond strength (X1) to the fracture strain (Y1) (X1 / Y1) is preferably 550 N / mm or more, and more preferably 600 N / mm or more.

[0056] The methods for determining peel bond strength (X1) and fracture strain (Y1) are as described in the examples described later.

[0057] By making the ratio of the aforementioned peel bond strength (X1) to the fracture strain (Y1) (X1 / Y1) less than 1200 N / mm, the energy storage modulus E' can be adjusted to the specified range.

[0058] When the ratio of peel bond strength (X1) to fracture strain (Y1) (X1 / Y1) is within the aforementioned range, it has the following characteristics: Figure 2 As shown by the line on the right, compared to the prior art where the holding part and the work-processed part are abruptly disconnected ( Figure 2 (Left side) In the compression shear bonding test, the slope of the "stress-strain curve" becomes gentler, and the inhibited holding part and the processed part break off sharply. The processed part is not easy to break, and the peeling also takes time.

[0059] This characteristic can be used to mitigate vibrations during processing and improve the machining accuracy when using CAD / CAM machines.

[0060] Furthermore, from the viewpoint that the workpiece is less likely to detach from the holding part and / or partially detach from the workpiece under low temperature conditions, and / or that the processing accuracy is excellent and the temperature stability is high, the ratio (X2 / X1) of the peel bond strength (X2) of the processed part and the holding part after storage at -30°C in the compression shear bonding test to the peel bond strength (X1) at 20°C is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0061] From the viewpoint that the workpiece and the retaining part are less likely to separate during processing and / or transportation, the aforementioned peel bond strength (X1) is preferably 100N or more, more preferably 150N or more, further preferably 200N or more, and most preferably 300N or more.

[0062] From the viewpoint that the workpiece and the holding part are less likely to separate during processing and / or transportation, the aforementioned peel bond strength (X1) is preferably within the aforementioned range regardless of the measurement temperature.

[0063] For example, the peel bond strength (X2) after storage at -30°C is preferably within the same range as the aforementioned peel bond strength (X1).

[0064] From the viewpoints of mitigating vibrations during processing, increasing processing accuracy, and preventing separation of the workpiece from the holding part during processing and / or transportation, the fracture strain (Y1) at 20°C is preferably 0.38 mm or more, more preferably 0.50 mm or more, and even more preferably 0.55 mm or more.

[0065] Furthermore, from the viewpoint of less strain and higher processing accuracy during processing, the aforementioned fracture strain (Y1) is preferably 1.0 mm or less, more preferably 0.90 mm or less, and even more preferably 0.80 mm or less.

[0066] From the viewpoint that the workpiece and the holding part are less likely to separate during processing and / or transportation, the aforementioned fracture strain (Y1) is preferably within the aforementioned range regardless of the measurement temperature.

[0067] For example, the fracture strain (Y2) of the processed part and the holding part after storage at -30°C in the compression shear bonding test (hereinafter also referred to as "fracture strain (Y2)" or "fracture strain (Y2) after storage at -30°C") is preferably within the same range as the aforementioned fracture strain (Y1).

[0068] In the grinding blank assembly of the present invention, an adhesive composition forms a layer that is held between the processed portion and the holding portion.

[0069] From the viewpoint that the loss coefficient tanδ is easily within the desired range when the prescribed adhesive composition is used in the first embodiment and / or that the ratio (X1 / Y1) of the peel bond strength (X1) to the fracture strain (Y1) is easily within the desired range in the second embodiment, the thickness of the aforementioned layer is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 15 μm or more.

[0070] Furthermore, from the viewpoint that the aforementioned loss coefficient tanδ is easily within the desired range when the prescribed adhesive composition is used in the first embodiment and / or that the ratio (X1 / Y1) of the aforementioned peel bond strength (X1) to the fracture strain (Y1) is easily within the desired range in the second embodiment, the thickness of the aforementioned layer is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 200 μm or less.

[0071] It should be noted that since bonding is performed under a constant load during the manufacturing of the grinding blank assembly, the thickness of the adhesive layer is considered to have no thickness deviation. However, in cases where thickness deviation occurs, the minimum thickness can be set as the thickness of the adhesive layer.

[0072] In the grinding blank assembly of the present invention, from the viewpoint of being suitable for processing with a CAD / CAM machine and having sufficient mechanical strength as a dental patch, in the first embodiment and / or the second embodiment, the Vickers hardness of the processed part is preferably 40HV 5 / 30 or more, more preferably 60HV 5 / 30 or more, further preferably 65HV 5 / 30 or more, and most preferably 70HV 5 / 30 or more.

[0073] Furthermore, from the viewpoint of being suitable for processing using a CAD / CAM machine and having sufficient mechanical strength as a dental patch, in the first embodiment and / or the second embodiment, the Vickers hardness of the processed part is preferably 140HV 5 / 30 or less, more preferably 135HV 5 / 30 or less, even more preferably 130HV 5 / 30 or less, and most preferably 125HV 5 / 30 or less.

[0074] The Vickers hardness test can be performed according to JIS Z 2244:2009.

[0075] "HV 5 / 30" means that the test force is maintained at a load of 5 kgf for 30 seconds.

[0076] If the specimen is broken and / or lacks indentation due to HV 5 / 30, it can be replaced with HV 1 / 10.

[0077] Therefore, in this specification, the Vickers hardness of the aforementioned processed part can also be understood as "preferably 40HV 1 / 10 or higher".

[0078] In the grinding blank assembly described in the first and / or second embodiments of the present invention, from the viewpoint that the ratio (X1 / Y1) of the loss coefficient tanδ at 20°C and / or the peel bond strength (X1) to the fracture strain (Y1) is within the aforementioned desired range, the adhesive composition preferably contains at least one selected from epoxy-modified silicone compounds, (meth)acrylate compounds, and urethane compounds. From the viewpoint that it sufficiently mitigates vibrations generated during processing using a CAD / CAM machine, exhibits excellent processing accuracy, and has high adhesion and water resistance, epoxy-modified silicone compounds are more preferred.

[0079] The adhesive composition can be used alone or in combination of two or more compounds. However, when using cyanoacrylate compounds, it is not possible to sufficiently increase the adhesive properties while reducing the elastic properties, and it is not possible to set the loss coefficient tanδ and / or the ratio (X1 / Y1) of the peel bond strength (X1) to the fracture strain (Y1) at 20°C to the aforementioned desired range. Therefore, the adhesive composition is preferably free of cyanoacrylate compounds.

[0080] The adhesive composition can be in the form of a single-component or a two-component formulation.

[0081] As for the aforementioned epoxy-modified organosilicon compounds, there are no particular limitations on the substances obtained by reacting modified organosilicon resin with epoxy resin, and they can be used.

[0082] As for the epoxy resin, there are no particular limitations as long as the effects of the present invention are achieved, and known epoxy resins (such as bisphenol A type epoxy resin, etc.) can be used.

[0083] As for the modified organosilicon resin, there are no particular limitations as long as the effects of the present invention are achieved, and known modified organosilicon resins can be used.

[0084] Epoxy-modified silicone compounds can form island structures in which epoxy resin domains are dispersed within a soft matrix phase of the modified silicone resin. It can be considered that by possessing this structure, the modified silicone resin exhibits characteristics of rubbery elasticity after curing, while also retaining the excellent adhesive properties of epoxy resin. Furthermore, during the curing process, the modified silicone resin is endowed with a continuous phase, while the epoxy resin undergoes a fine dispersion morphology.

[0085] As the epoxy-modified silicone compound used in this invention, commercially available products can be used in a range that allows the loss coefficient tanδ and / or the ratio (X1 / Y1) of the peel bond strength (X1) to the fracture strain (Y1) at 20°C to be set within the aforementioned desired range.

[0086] Commercially available products include: "EP001K" (trade name, two-component epoxy-modified silicone elastic adhesive, main component: epoxy resin, curing agent: modified silicone polymer, Tg: -65℃, manufactured by CEMEDINE), which can be used in a wide temperature range of -40 to 100℃; "EP001N" (trade name, two-component epoxy-modified silicone elastic adhesive, main component: epoxy resin (bisphenol A type epoxy resin), curing agent: modified silicone resin, manufactured by CEMEDINE), which can be used in a wide temperature range of -60 to 120℃; "BONDEFLEX (registered trademark)" (trade name, single-component room temperature curing epoxy-modified silicone resin, manufactured by KONISHI), which can be used in a wide temperature range of -30 to 80℃; and "BOND," which can be used in a wide temperature range of -60 to 120℃. Elastic adhesives such as MOS-8 (trade name, two-component epoxy-modified silicone resin, manufactured by KONISHI Corporation) that have rubber-like elasticity after curing are preferred from the viewpoint that they can more easily mitigate vibrations generated during processing using CAD / CAM machines.

[0087] From the viewpoint that the loss coefficient tanδ and / or the ratio (X1 / Y1) of the peel bond strength (X1) to the fracture strain (Y1) at 20°C are easily within the aforementioned desired range, examples include (meth)acrylic acid modified organosilicon compounds, butyl acrylate having long-chain alkyl groups in the side chain, 2-ethylhexyl acrylate, etc., among which acrylic acid modified organosilicon compounds are preferred.

[0088] (Meth)acrylate compounds can be used in commercially available products in a range that allows the loss coefficient tanδ and / or the ratio of peel bond strength (X1) to fracture strain (Y1) (X1 / Y1) at 20°C to be set within the aforementioned desired range.

[0089] Commercially available products include "SUPER X No. 8008" (trade name, single-component room temperature curing acrylic modified silicone resin elastic adhesive, Tg: -63℃, manufactured by CEMEDINE), which are elastic adhesives that have rubber-like elasticity after curing.

[0090] Adding low molecular weight (meth)acrylic acid compounds to (meth)acrylic acid compounds can shift the peak of tanδ to the low-temperature side.

[0091] Carbamate compounds have carbamate bonds, and the unique microphase separation structure of carbamate resins can be controlled by the addition reaction (urethane reaction) of polyisocyanates and polyols.

[0092] The aforementioned microphase separation structure consists of two phases: hard domains and soft domains.

[0093] Hard domains function as hard segments with high cohesive energy urethane bonds formed by hydrogen bonding, while soft domains consist of low cohesive energy methylene chains, ethers, and ester bonds. This combination of hard and soft domains results in high toughness and flexibility, effectively mitigating vibrations generated during machining using CAD / CAM machines.

[0094] As a urethane compound, commercially available products can be used in a range that allows the loss coefficient tanδ and / or the ratio of peel bond strength (X1) to fracture strain (Y1) (X1 / Y1) at 20°C to be set within the aforementioned desired range.

[0095] In the first and second embodiments, the processed part preferably includes oxide ceramic, and more preferably includes dental oxide ceramic.

[0096] Examples of dental oxide ceramics include zirconia, alumina, and glass ceramics. Dental oxide ceramics can be used alone or in combination of two or more types.

[0097] When the dental oxide ceramic is zirconia, the zirconia may contain a stabilizer (hereinafter also referred to as "stabilizer") capable of inhibiting the zirconia phase transformation. The aforementioned stabilizer is preferably capable of forming partially stabilized zirconia.

[0098] The zirconia in the processed part can be a zirconia molded body or a zirconia pre-fired body.

[0099] Zirconia molded bodies are obtained by applying external force to powder containing zirconia particles and shaping it. They are objects before calcination, which means that necking (fixation) has not occurred.

[0100] When manufacturing zirconia molded bodies using a method that involves pressing powder containing zirconia particles into shape, the specific method of pressing is not particularly limited, and a known pressing machine can be used.

[0101] Zirconia pre-sintered bodies can serve as precursors (intermediate products) for zirconia sintered bodies. In this specification, zirconia pre-sintered body refers to an object in which zirconia particles are necked (fixed) and not fully sintered. Zirconia pre-sintered bodies can be obtained by pre-firing the aforementioned zirconia molded body.

[0102] To reliably achieve block formation, the calcination temperature (pre-calcination temperature) in the pre-calcination process is preferably 800°C or higher, more preferably 900°C or higher, and even more preferably 950°C or higher. Furthermore, the pre-calcination temperature is preferably below 1200°C, more preferably below 1150°C, and even more preferably below 1100°C.

[0103] Examples of stabilizers mentioned above include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y₂O₃), cerium oxide (CeO₂), scandium oxide (Sc₂O₃), niobium oxide (Nb₂O₅), lanthanum oxide (La₂O₃), erbium oxide (Er₂O₃), and praseodymium oxide (Pr₆O₃). 11 Among oxides such as Pr2O3, samarium oxide (Sm2O3), europium oxide (Eu2O3), and thulium oxide (Tm2O3), yttrium oxide is preferred from the viewpoint that the sintered zirconia body has excellent light transmittance.

[0104] From the viewpoint of excellent light transmittance of zirconia sintered bodies, the content of the stabilizer (suitably yttrium oxide) in the aforementioned zirconia is preferably 3.0 mol% or more, more preferably 3.5 mol% or more, and even more preferably 4.0 mol% or more, relative to the total molar content of zirconia (zirconia (IV); ZrO2) and the stabilizer. When the content is 3.0 mol% or more, the cubic crystal system in the sintered body increases, which improves the light transmittance of the zirconia sintered body. Furthermore, the content of the aforementioned stabilizer is preferably 7.5 mol% or less, more preferably 7.0 mol% or less, and even more preferably 6.5 mol% or less. When the content is 7.5 mol% or less, the reduction in strength of the zirconia sintered body can be suppressed. This range can be formed by any combination of these.

[0105] In both the first and second embodiments, the retaining part can be made of materials such as aluminum alloys or iron alloys, as long as it can secure the workpiece. Examples of materials include aluminum and its alloys, iron and its alloys, pure iron, cast iron, stainless steel (SUS304, SUS316, etc.), nickel alloys (nickel-aluminum alloys, nickel-chromium alloys, etc.), chromium alloys, cobalt alloys, carbon steel, manganese steel (SMn420, SMn433, SMn438, SMn443, etc.), invar alloys, molybdenum, copper, bronze, silver, gold, and platinum. The composition of the aforementioned alloys is not limited as long as they are included within the range considered as such alloys; for example, in a cobalt alloy, a cobalt content of 42-65% is acceptable. Among the aforementioned materials, those with a coefficient of thermal expansion similar to that of the workpiece are suitable. The retaining part can be made of one material alone or in combination of two or more materials.

[0106] The grinding blank assembly of the present invention is particularly suitable for dental applications.

[0107] The manufacturing method of the grinding blank assembly of the present invention can be exemplified by the following manufacturing method: which includes a step of curing an adhesive composition to bond the part to be processed to the holding part, wherein the adhesive composition is any of the following (excluding cyanoacrylate compounds).

[0108] (i) A mixture obtained by mixing epoxy resin with an organosilicon-modified polymer; (ii) A mixture obtained by mixing (meth)acrylic monomers and / or (meth)acrylic oligomers with modified organosilicon; or (iii) At least one carbamate compound.

[0109] As an example of an adhesive composition (i), the mixture obtained by mixing epoxy resin and silicone-modified polymer is not particularly limited in that it functions as an epoxy-modified silicone compound and is able to adjust the loss coefficient tanδ and / or the ratio of peel bond strength (X1) to fracture strain (Y1) (X1 / Y1) to the aforementioned desired range, and commercially available products can be used.

[0110] As an embodiment (ii) of the adhesive composition, the mixture obtained by mixing at least two of acrylic monomers and / or (meth)acrylic oligomers is not particularly limited as long as the loss coefficient tanδ and / or the ratio (X1 / Y1) of peel bond strength (X1) to fracture strain (Y1) can be adjusted to the aforementioned desired range, and commercially available products (suitable such as acrylic modified silicone compounds) can be used.

[0111] As an embodiment (iii) of the adhesive composition, at least one urethane compound may be used, provided that the loss coefficient tanδ and / or the ratio of peel bond strength (X1) to fracture strain (Y1) (X1 / Y1) can be adjusted to the aforementioned desired range, and there are no particular limitations.

[0112] There are no particular limitations on the process of curing the adhesive composition to bond the processed part and the retaining part, and known methods can be used to bond them.

[0113] like Figure 1 A and Figure 1 As shown in B, the range of coating adhesive compositions is not limited as long as they can bond the processed part to the holding part and satisfy conditions [1] and / or conditions [2], and can be appropriately selected.

[0114] The amount of adhesive composition applied can be appropriately selected so that the cured adhesive layer is within the aforementioned desired range.

[0115] As long as the effects of the present invention are achieved, the present invention includes embodiments formed by combining all or part of the above embodiments in various ways within the scope of the technical concept of the present invention.

[0116] Implementations that combine conditions [1] and [2] (implementations where the loss coefficient tanδ at 20°C is within the aforementioned desired range, and the ratio of peel bond strength (X1) to fracture strain (Y1) (X1 / Y1) is within the aforementioned desired range) are also included in this invention. Example

[0117] Next, embodiments are listed to illustrate the present invention in more detail. However, the present invention is not limited to these embodiments at all, and those skilled in the art can make various modifications within the scope of the technical concept of the present invention.

[0118] The types of adhesives used in the embodiments and comparative examples described below are as follows.

[0119] Epoxy-modified silicone resin "EP001K": A two-component epoxy-modified silicone elastic adhesive (trade name "EP001K", main component: epoxy resin, curing agent: modified silicone polymer, Tg: -65℃, manufactured by CEMEDINE). Epoxy-modified silicone resin "EP001N": A two-component epoxy-modified silicone elastic adhesive (trade name "EP001N", manufactured by CEMEDINE). Epoxy-modified silicone resin "MOS-8": A two-component epoxy-modified silicone elastic adhesive (trade name "BOND MOS-8", manufactured by KONISHI Corporation). High-Super 5 epoxy resin: a two-component epoxy adhesive (trade name "High-Super 5", manufactured by CEMEDINE). Aron α403X, a cyanoacrylate resin: a cyanoacrylate adhesive (trade name "Aron α403X", manufactured by Toa Synthetic Co., Ltd.) It should be noted that the above adhesives are all used by mixing the main agent and the curing agent according to the instructions accompanying the product, and then applying them to the specified positions of the retaining part after several minutes.

[0120] [Example 1] The substances described in Table 1 are used as the processed part, the retaining part, and the adhesive composition.

[0121] At room temperature (20°C), epoxy-modified silicone is applied to the workpiece and the holding part is joined together with the adhesive layer formed after curing, so that the adhesive layer is the thickness shown in Table 1. Then, a load is applied to achieve the specified adhesive layer thickness, and the adhesive composition is cured at room temperature to manufacture a grinding blank assembly.

[0122] The following methods were used to evaluate the physical properties of the resulting grinding blank assembly, the processed part of the material, or the adhesive composition. The results of each physical property are summarized in Table 1 below.

[0123] [Examples 2-5 and Comparative Example 1] The thickness of the workpiece, the holding part, the adhesive composition, and the adhesive layer are changed to those described in Table 1. Otherwise, the same procedure as in Example 1 is followed to manufacture the grinding blank assembly.

[0124] [Determination of Vickers hardness of the machined part] The Vickers hardness of the machined part was measured according to JIS Z 2244:2009.

[0125] The Hv value (arithmetic mean of n=10) was calculated using a micro / macro Vickers hardness tester (trade name "Falcon500", manufactured by Innovatest Japan) with a load of 5 kgf held for 30 seconds.

[0126] [Determination of the thickness of the cured adhesive composition (thickness of the adhesive layer)] The aforementioned prepared grinding blank assembly was cut, and the thickness of the cured adhesive composition in the cut surface was measured as the thickness of the adhesive layer. The thickness of the adhesive layer of the cured adhesive composition was measured using an optical microscope (DIGITAL MICROSCOPE KH-7700: HIROX) (n=1).

[0127] It should be noted that since the bonding was performed under a constant load during the manufacturing of the grinding blank assembly, the thickness of the bonding layer is considered to have no thickness deviation.

[0128] [Determination of dynamic viscoelasticity in ultra-micro indentation testing (nanopioid analyzer)] Dynamic viscoelasticity was determined using an ultra-micro indentation hardness tester ("ENT-5X", ELIONIX) by the following method.

[0129] Remove the holding part from the aforementioned prepared grinding blank assembly, and use the cured portion of the adhesive composition remaining only on the holding part side for measurement.

[0130] The testing machine used was an ultra-micro indentation hardness tester (ENT-5X, ELIONIX). The storage modulus E' and loss modulus E" of the cured adhesive composition were determined under the following conditions. The loss coefficient tanδ = E" / E' was calculated based on the measured values.

[0131] For one test piece of each embodiment and comparative example, the measurement interval was set to 100 μm, and data from 3 points were obtained at each of the following set temperatures, and the arithmetic mean was calculated.

[0132] <Measurement Conditions> Test load: 200 μN Loading and unloading time: 10 seconds (divided into 500 steps, with a step interval of 20 milliseconds). Load holding time: 5 seconds Vibration frequency: 1.0Hz Vibration time: 10 seconds Amplitude: 20μN Set temperature: 20℃ and -30℃ Indenter: Bodeich indenter Correction method in the analysis: Oliver method.

[0133] [Compression-shear bond test: determination of peel bond strength] Fix the retaining part 2 (so that...) Figure 1 (B rotates 90 degrees and is fixed laterally). In the workpiece 1, a load is applied using a support roller at a distance of 18 mm from the bonding surface (the surface bonded to the workpiece). The load is measured when the workpiece 1 is peeled off from the holding part 2 using a benchtop precision universal testing machine (Autograph AGS-5kNX, manufactured by Shimadzu Corporation). The test is performed at a descent speed of 1.0 mm / s for the support roller.

[0134] Regarding the peel bond strength, after bonding the processed part 1 to the holding part 2, the test is performed after standing at 20°C for 1 day, or after bonding, the test is performed after standing at 20°C for 1 day, then standing at -30°C for 1 day, and then standing at 20°C for 1 day (arithmetic mean of n=5).

[0135] The bonding area (the bonding area between the holding part 2 and the workpiece 1) in each grinding blank assembly used in the aforementioned peel bond strength test was 317 mm. 2 It should be noted that the aforementioned bonding area is based on the total area of ​​the retaining part 2 bonded to the workpiece part 1 (viewed from a top longitudinal view). Figure 1 When B, the area of ​​the overlapping part between the holding part 2 and the processed part 1 is used for calculation.

[0136] As for the peel bond strength (X1) at 20°C, from the viewpoint that the workpiece is not easily detached from the holding part during the processing of the workpiece, it is preferably 100N or more, more preferably 150N or more, further preferably 200N or more, and most preferably 300N or more.

[0137] The peel bond strength (X2) at -30°C is preferably in the same range as the peel bond strength (X1) at 20°C.

[0138] [Compression-shear bonding test: determination of fracture strain] The displacement is read from the stress-strain curve obtained in the aforementioned [Compression Shear Bond Test: Determination of Peel Bond Strength], and is set as the fracture strain (arithmetic mean of n=5).

[0139] Regarding fracture strain, similar to peel bond strength, it was measured after bonding and standing at 20°C for 1 day, or after bonding and standing at 20°C for 1 day, then standing at -30°C for 1 day, and then standing at 20°C for 1 day (arithmetic mean of n=5).

[0140] From the viewpoints of mitigating vibrations during processing, increasing processing accuracy, and preventing separation of the workpiece from the holding part during processing and / or transportation, the fracture strain (Y1) at 20°C is preferably 0.38 mm or more, more preferably 0.50 mm or more, and even more preferably 0.55 mm or more.

[0141] Furthermore, from the viewpoint of less strain and higher processing accuracy during processing, the fracture strain (Y1) is preferably 1.0 mm or less, more preferably 0.90 mm or less, and even more preferably 0.80 mm or less.

[0142] The fracture strain (Y2) at -30°C is preferably in the same range as the fracture strain (Y1) at 20°C.

[0143] [Evaluation of machining accuracy] Based on the three-dimensional NC data, the obtained grinding blank assembly was machined into the specified shape of a dental patch (arithmetic mean of n=10) using a milling machine (trade name "DWX-52DC", manufactured by Roland DG) with an unused KATANA (registered trademark) drill bit (manufactured by Kuraray Noritake Dental Co., Ltd., Φ2mm, uncoated with diamond).

[0144] The following criteria are used to evaluate machining accuracy. A: It can be processed into dental repair parts of the target size. B: There was one instance where a dental restoration of the target size could not be obtained. C: There were more than two instances where dental restorations of the target size could not be obtained. D: Dental fillings that cannot be made to the target size.

[0145] [Table 1]

[0146] Based on the above results, it can be confirmed that the grinding blank assembly of the present invention can effectively mitigate vibrations generated during processing using a CAD / CAM machine, and the processing accuracy is also excellent.

[0147] Industrial utilization The grinding blank assembly of the present invention is useful in dental applications, as it can effectively mitigate vibrations caused by the rotation of the grinding rod during processing, thus resulting in excellent processing accuracy.

[0148] In addition, the grinding blank assembly of the present invention can also effectively mitigate vibrations during product transportation, thus reducing the amount of cushioning material when packaging products, thereby reducing environmental impact and / or minimizing product boxes.

[0149] Explanation of reference numerals in the attached figures 1. Processed part 2. Holding section 3. Adhesive Composition

Claims

1. A grinding blank assembly comprising a workpiece portion, a retaining portion and an adhesive composition, and satisfying the following conditions [1] and / or [2]: [1] The cured adhesive composition has a loss coefficient tanδ of less than 0.70 at 20°C in an ultra-micro indentation test (nanoindenter); [2] The ratio (X1 / Y1) of the peel bond strength (X1) and the fracture strain (Y1) of the processed part and the retaining part in the compression shear bonding test at 20°C is less than 1200 N / mm.

2. The grinding blank assembly according to claim 1, wherein, The cured adhesive composition exhibits a storage modulus E' of 200 N / mm² at 20°C in an ultramicro indentation test. 2 the following.

3. The grinding blank assembly according to claim 1 or 2, wherein, The cured adhesive composition exhibits a loss modulus E” of 100 N / mm² at 20°C in an ultra-micro indentation test. 2 the following.

4. The grinding blank assembly according to claim 1, wherein, The peel bond strength (X1) at 20°C in the compression shear bond test is above 100N.

5. The grinding blank assembly according to claim 1 or 4, wherein, The fracture strain (Y1) at 20°C in the compression-shear bonding test was 0.38~1.0 mm.

6. The grinding blank assembly according to any one of claims 1, 2, or 4, wherein, The adhesive composition forms a layer that is held between the processed portion and the holding portion. The thickness of the layer is 5~500μm.

7. The grinding blank assembly according to any one of claims 1, 2, or 4, wherein, The Vickers hardness of the machined part, as measured according to JIS Z 2244:2009, is 40~140HV 5 / 30.

8. The grinding blank assembly according to any one of claims 1, 2, or 4, wherein, The adhesive composition comprises at least one selected from epoxy-modified silicone compounds, (meth)acrylic compounds, and urethane compounds, excluding cyanoacrylate compounds.

9. The grinding blank assembly according to any one of claims 1, 2, or 4, wherein, The processed part comprises oxide ceramic.

10. The grinding blank assembly according to any one of claims 1, 2, or 4, wherein, The processed part comprises at least one selected from zirconium oxide, alumina, and glass ceramics.

11. The grinding blank assembly according to any one of claims 1, 2, or 4, wherein, The retaining part comprises aluminum alloy and / or iron alloy.

12. The grinding blank assembly according to any one of claims 1, 2 or 4, for dental use.

13. A method for manufacturing the grinding blank assembly according to any one of claims 1, 2, or 4, comprising a step of curing an adhesive composition to bond the part to be processed to the holding part. The adhesive composition is any of the following, but does not include cyanoacrylate compounds. (i) A mixture obtained by mixing epoxy resin with an organosilicon-modified polymer; (ii) A mixture obtained by mixing (meth)acrylic monomers and / or (meth)acrylic oligomers with modified organosilicon; or (iii) At least one carbamate compound.

Citation Information

Patent Citations

  • Dental mill blank assembly

    JP2018076272A

  • Dental mill blank assembly

    JP2020068873A

  • Zirconia mill blank and its manufacturing method

    JP2020151235A